Automatic duration modeling and time-scale modification of Filipino speech - Asis, Juan Paolo (2005)
The project is a Filipino text-to-speech synthesizer based on data from the Filipino Speech Corpus (FSC). The project is divided into two main modules, the Natural Language Processing module (NLP), and the Digital Signal Processing module (DSP). The NLP takes in text and gives out the chain of speech units, and the pitch and duration of each, while the DSP takes these three pieces of information and gives out synthesized speech. For this project, phones were used as speech units at the NLP level. A Classification and Regression Tree is used as a model for the duration, trained from the Paragraph-Sentence sub-corpus of the FSC, using certain features extracted from the text. These features are the current, next, and previous phone, the relative position in the syllable, word, and sentence, respectively. In the DSP, a concatenative synthesizer was used to produce the synthesized speech. Syllables from the Syllable sub-corpus of the FSC were used as units of synthesis. The Time-Domain Pitch-Synchronous OverLap-Add method (TD-PSOLA) was used as the method of synthesis of the syllable waveforms. Overlap rules were generated to concatenate the synthesized syllable waveforms. The synthesized speech was tested with listeners using the Mean Opinion Score (MOS) method, which is a scale from 1 (Bad) n 5 (Excellent). The duration model and the syllable synthesis were applied separately. The results of the listening tests show that the duration model is acceptable when applied to the original waveform, with MOSs of 3.7 and 3 for the female and the male speaker, respectively. The syllable synthesis method, however, needs improvement, with MOSs of 2.3 and 2.